¿Matar dos pájaros de un tiro? : La inclusión de mujeres de origen inmigrante en las listas municipales de los partidos políticos en españa 2011-2015 - Escobar Villegas, Soledad; Pérez-Nievas, Santiago; Cordero, Guillermo (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2021)
This article analyses the descriptive representation of immigrant-origin women in two local Spanish elections. On the basis of the influence of political opportunity structures and the role played by political parties, we quantify their presence on party lists and their degree of success in becoming councilwomen. Using the APREPINM database we compare their levels of representation across different immigrant-origin minorities and the degree of gender disparity within each group. Our results show that women originating from the EU and Latin America benefit from greater access to party lists than their male counterparts and their female peers from other groups. But when it comes to being elected as councilwomen, only Latin-American women maintain this comparative advantage.
Keywords: immigration; gender; political integration; women candidates; political parties